Basic proposal for evaluation of plant genetic resources to generate new crops - Flores-Sánchez, I. Darío; Sandoval-Villa, Manuel; Trejo-Téllez, Libia Iris (Frontiers in Plant Science, 2025)
Given the reduced diversity of foods available in production systems, a factor linked to malnutrition in society, it is necessary to evaluate new plant genetic resources for human consumption. Underutilized or abandoned plant species, wild, semi-domesticated or domesticated, are an alternative to this problem. However, the lack of skills in people interested in this species, and the little attention paid to these resources in research centers, leads to a lack of basic data on characterization and evaluation, and makes it difficult to identify germplasm with potential for improvement purposes or for direct use. The objective of the proposal is to raise a basic theme to characterize and evaluate plant genetic resources in greenhouses and hydroponics, to propose and generate alternative crops with topics such as seed germination, traits of agronomic interest, nutrient absorption, phenology, fruit quality and secondary metabolites, which serves as a methodological guide, and meets the recommendations of the World Health Organization (WHO) and the Food and Agricultural Organization of the United Nations (FAO), on the need to generate data for the use of the biodiversity of underutilized or abandoned species, which will allow to increase the diversity of foods with important nutrimental content for the population.